INOVASI PEMBELAJARAN PAI DI SEKOLAH DASAR: INTEGRASI E-DISCOVERY LEARNING DALAM FLIPPED CLASSROOM - Qurratina, Noor Shania; Irma Soraya; Mohammad Kurjum (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The development of technology has changed all aspects of human life, including the way of learning and accessing information. At the elementary school level, the integration of technology in Islamic Religious Education learning is still rarely done. Therefore, this study aims to explore a form of Islamic Religious Education learning innovation by integrating technology in the form of e-discovery learning and flipped classroom at the elementary school level. This study is a type of library research that collects data using literature studies and is analyzed using qualitative data analysis techniques. The results of this study indicate that the use of e-discovery learning applications with flipped classroom strategies in Islamic Religious Education learning in elementary schools is relevant to overcoming learning problems in the classroom in the form of limited time and learning resources.